“Picking up signals” in male genital morphospace and integrating phylogenomics to delimit Neotropical Nylanderia Emery species (Hymenoptera: Formicidae) - Williams, Jason L. (2024)
Genital morphology, a cornerstone in taxonomy that predates Linnaeus’s Systema Naturae, is vital for species delimitation. However, the widely accepted paradigm that genitalia are taxonomically informative lacks robust testing between closely related species, and supporting evidence is often limited to taxonomic literature in which genitalia are assumed a priori to be species-specific. The cosmopolitan ant genus Nylanderia Emery includes 123 described species, with most in the Neotropics still undescribed. Workers are often morphologically cryptic, and males are rare in collections but required for morphological delimitation. Using Ultraconserved Elements (UCEs) from 236 samples, including 53 Neotropical Nylanderia species, we reconstructed a phylogeneticframework to compare the genitalia (gonopods) of males collected alongside workers. We used geometric morphometrics on images of slide-mounted genitalia from 16 species and nano-CT scans of Nylanderia fulva (Mayr) and Nylanderia pubens (Forel) genital capsules and interpreted results considering phylogeny under maximum likelihood and the multispecies coalescent. We found strong morphological and molecular support for 2 distantly related American clades, identifiable by gonopod shape, with significant differences observed among most species. Three previously reported COI clades of N. fulva were not supported as monophyletic, nor were their gonopods significantly different. However, N. pubens was supported as distinct by allphylogenetic and 3DGM results. Our findings emphasize the importance of male genitalia for delimiting species boundaries and revising Neotropical Nylanderia. Given their importance, particularly in morphologically cryptic taxa, we recommend a greater focus on linking male and worker phenotypes, which can be facilitated through comprehensive nest series collection.